INDICATIONS FOR SURGICAL TREATMENT, CLASSIFICATION OF SCOLIOTIC SPINAL DEFORMITIES - Fatxulla R. Umarkhodjaev (Central Asian Journal of Medicine, 2024)
This article analyses the classification of various forms of scoliosis. Indications and contraindications for surgical treatment of scoliotic disease in children and adolescents have been determined.